CGIAR joins forces with WFP and Norad to enhance climate resilience and food security in Sub-Saharan Africa - Abay, Kibrom A.; Kosec, Katrina; Anisimova, Evgeniya (CGIAR, 2023)
CGIAR, the world’s largest agricultural innovation network, has joined forces with the World Food Programme (WFP) and the Norwegian Agency for Development Cooperation (Norad) under the project titled, “Learning Support for a Sub-Saharan Africa Multi-Country Climate Resilience Program for Food Security.”